FROM VIOLENCE TO CONSUMER BEHAVIOR: A LITERATURE REVIEW OF TREND AND METHOD OF CULTIVATION THEORY AS A GUIDING FRAMEWORK IN EBSCO ELECTRONIC DATABASE FROM 1980 TO 2009 - Kresno Agus author (Universitas Gunadarma, 2011)
Not only in Indonesia, but also in others country watching television is a major activity. The Cultivation theory (sometimes referred to as the cultivation hypothesis or cultivation analysis) suggests that when people watch television they are acquiring or cultivating a view of the “real world” that is shaped by the way things are portrayed on television. The objective of this study is to describe how the research using the cultivation theory as the guiding framework or theoretical base is performed in the the published scientific articles. Data collected is analyzed using content analysis method. The overall findings indicate that in initial development of cultivation theory, publication articles focused more on the falsification of cultivation theory itself, cultivation theory has been confirmed in a wide array of studies across diverse fields area attests to its versatility. But in later development, the theory was also used in the analysis of the theme of non-violence, such as psychology and economy. In economy, the focus is primarily on consumer behavior; the large majority of articles were empirical research (70%), most of all collecting data in literature research used survey method (72.7%), empirical research has been used variable control (57.4%). The controlled variables were general demographics, such as age, gender, income, ethnic, and education.